Temporal genetic stability in natural populations of the waterflea Daphnia magna in response to strong selection pressure. Issue 24 (25th November 2016) - Orsini, Luisa; Marshall, Hollie; Cuenca Cambronero, Maria; Chaturvedi, Anurag; Thomas, Kelley W.; Pfrender, Michael E.; Spanier, Katina I.; De Meester, Luc
Abstract: Studies monitoring changes in genetic diversity and composition through time allow a unique understanding of evolutionary dynamics and persistence of natural populations. However, such studies are often limited to species with short generation times that can be propagated in the laboratory or few exceptional cases in the wild. Species that produce dormant stages provide powerful models for the reconstruction of evolutionary dynamics in the natural environment. A remaining open question is to what extent dormant egg banks are an unbiased representation of populations and hence of the species' evolutionary potential, especially in the presence of strong environmental selection. We address this key question using the water flea Daphnia magna, which produces dormant stages that accumulate in biological archives over time. We assess temporal genetic stability in three biological archives, previously used in resurrection ecology studies showing adaptive evolutionary responses to rapid environmental change. We show that neutral genetic diversity does not decline with the age of the population and it is maintained in the presence of strong selection. In addition, by comparing temporal genetic stability in hatched and unhatched populations from the same biological archive, we show that dormant egg banks can be consulted to obtain a reliable measure of genetic diversity over time, at least in the multidecadal time frame studied here. The stability of neutral genetic diversity through time is likely mediated by the buffering effect of the resting egg bank.